Implementasi Balanced Scorecard pada Unit Usaha Kecil Menengah: Studi Kasus sebuah Restoran di Jakarta - Widaningrum, Dyah Lestari; Kabul, Ivanaldy (Bina Nusantara University, 2014)
Increasing competition requires companies both large and small, to be more productive and innovative, therefore, companies need to be supported by an effective performance measurement system. In this research, the implementation of a balanced scorecard in SMEs engaged in the management of a restaurant, for a chance to be more superior and to compete amid the rapid development of the restaurant sector. Strategic map based on four perspective of Balanced Scorecard was defined, completed with agreement of strategic objective and measurement. This implementation give evidence that even with many limitations on SMEs, they have developed balanced scorecard, with adjustment based on condition for strategic objective performance indicator, so this performance measurement evaluation process is applicable and able to achieve the main objective, to provide information for continuous improvement process.